2014
DOI: 10.1007/s40272-014-0081-5
|View full text |Cite
|
Sign up to set email alerts
|

Results from a Nationwide Cohort Temporary Utilization Authorization (ATU) Survey of Patients in France Treated with Pheburane® (Sodium Phenylbutyrate) Taste-Masked Granules

Abstract: ObjectivesThe aim of this study was to describe a nationwide system for pre-marketing follow-up (cohort temporary utilization authorization [ATU] protocol; i.e., ‘therapeutic utilization’) of a new taste-masked formulation of sodium phenylbutyrate (NaPB) granules (Pheburane®) in France and to analyze safety and efficacy in this treated cohort of patients with urea cycle disease (UCD).MethodsIn October 2012, a cohort ATU was established in France to monitor the use of Pheburane® on a named-patient basis. All tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
18
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(18 citation statements)
references
References 12 publications
0
18
0
Order By: Relevance
“…4,7 Therapeutic Implications From a translational perspective, the current results identify a potential benefit of pharmacological inhibition of ER stress as a therapeutic strategy in clinical AF. Among the available compounds, 4PBA seems promising, because this compound is already approved for clinical use to treat urea cycle disorders 36,37,71 and is available under the trade names Buphenyl (available in the United States since 1996) and Ammonaps (available in Europe since 1999). 4PBA acts as a chemical chaperone and alleviates ER stress by protecting from aggregation of misfolded proteins.…”
Section: Prominent Role Of Er Stress-associated Autophagy In Cardiomymentioning
confidence: 99%
See 1 more Smart Citation
“…4,7 Therapeutic Implications From a translational perspective, the current results identify a potential benefit of pharmacological inhibition of ER stress as a therapeutic strategy in clinical AF. Among the available compounds, 4PBA seems promising, because this compound is already approved for clinical use to treat urea cycle disorders 36,37,71 and is available under the trade names Buphenyl (available in the United States since 1996) and Ammonaps (available in Europe since 1999). 4PBA acts as a chemical chaperone and alleviates ER stress by protecting from aggregation of misfolded proteins.…”
Section: Prominent Role Of Er Stress-associated Autophagy In Cardiomymentioning
confidence: 99%
“…Tachypacing (TP) augments levels of endoplasmic reticulum (ER) stress markers and the autophagy gene ATG12. A, Representative Western blot of phosphorylated eIF2a S51 (molecular weight [MW], 38), an ER stress marker, basal eIF2a (MW,36), and GAPDH levels during normal pacing (NP) or in response to TP for the indicated duration. B, Quantified data of the ratio of phosphorylated eIF2a S51 normalized for basal eIF2a protein levels (N=3).…”
mentioning
confidence: 99%
“…In addition, due to the palatability issues associated with sodium phenylbutyrate, in recent years, the scientific community has been interested in the development of taste-masked granules of this pediatric drug which will be very useful to improve treatment adherence [109]. To date, two clinical trials have shown that the recently developed taste-masked formulation of sodium phenylbutyrate granules improves quality of life in patients with UCDs [110, 111]. …”
Section: Expert Opinionmentioning
confidence: 99%
“…These results led the investigators to initiate the first French nationwide 1-year cohort study on 25 patients, of whom 21 were children 13. All of them suffered from UCD, and prior to introducing the taste-masked granule formulation of NaPB, all were maintained on another nitrous scavenger, either NaPB or sodium benzoate.…”
Section: Resultsmentioning
confidence: 99%